How do regional labor markets adjust to immigration? A dynamic analysis for post-war Germany - Sebastian Braun; Henning Weber (Kiel Institute for the World Economy (IfW), 2016)
We draw on two decades of historical data to analyze how regional labor markets in West Germany adjusted to one of the largest forced population movements in history, the mass inflow of eight million German expellees after World War II. The expellee inflow was distributed very asymmetrically across two West German regions. A dynamic two-region search and matching model of unemployment, which is exposed to the asymmetric expellee inflow, closely fits historical data on the regional unemployment differential and the regional migration rate. Both variables increase dramatically after the inflow and decline only gradually over the next decade. We show that despite the large and long-lasting dynamics following the expellee inflow, native workers experience only a modest loss in expected discounted lifetime labor income of 1.38%. Per-period losses in native labor income, however, are up to four times as large. The magnitude of income losses also depends on the initial location and labor market status of native workers. In counterfactual analyses, we furthermore show that economic policy interventions that affect the nature of the immigration inflow can effectively reduce native income losses and dampen adjustment dynamics in regional labor markets. One such intervention is to distribute the inflow more evenly over time. Smaller immigration inflows, similar in magnitude to the refugee inflow that Germany is experiencing today, also reduce native income losses markedly but decrease the duration of labor market adjustment only modestly.
Keywords: J61; F22; 330; Immigration; labor market adjustments; dynamic search and matching model of unemployment; asymmetric labor supply shock; post-war Germany